From Industry 4.0 to 5.0: leveraging AI and IoT for sustainable and human-centric operations - Hammad, Muhammad Yahya; Syed Radzi, Rahamaddulla; Puteri Fadzline, Muhamad Tamyez; Muhammad Ashraf, Fauzi (Elsevier Ltd, 2025)
Purpose: This study investigates the transition from Industry 4.0 to Industry 5.0, focusing on the integration of artificial intelligence (AI), machine learning (ML), and the Internet of Things (IoT) to support human-centric, sustainable and resilient production systems. It aims to identify key trends, challenges and opportunities within this evolving industrial paradigm.